Ethanol Effects Involve Non-canonical Unfolded Protein Response Activation in Yeast Cells - Navarro-Tapia, Elisabet; Pérez-Torrado, Roberto; Querol, Amparo (Frontiers in Microbiology, 2017)
The unfolded protein response (UPR) is a conserved intracellular signaling pathway that controls transcription of ER homeostasis related genes. Ethanol stress has been recently described as an activator of the UPR response in yeast Saccharomyces cerevisiae, but very little is known about the causes of this activation. Although some authors ensure that the UPR is triggered by the unfolded proteins generated by ethanol in the cell, there are studies which demonstrate that protein denaturation occurs at higher ethanol concentrations than those used to trigger the UPR. Here, we studied UPR after ethanol stress by three different approaches and we concluded that unfolded proteins do not accumulate in the ER under. We also ruled out inositol depletion as an alternative mechanism to activate the UPR under ethanol stress discarding that ethanol effects on the cell decreased inositol levels by different methods. All these data suggest that ethanol, at relatively low concentrations, does not cause unfolded proteins in the yeasts and UPR activation is likely due to other unknown mechanism related with a restructuring of ER membrane due to the effect of ethanol.